2007
DOI: 10.1016/j.exger.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in human aging

Abstract: Dendritic cells (DCs) play a critical role in linking innate and adaptive immunity. A role of DCs in immunosenescence and chronic inflammation associated with aging has not been investigated in detail. In this article we will briefly review DCs biology and changes associated with human aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 55 publications
(71 reference statements)
3
61
1
2
Order By: Relevance
“…Moreover, aging is associated with a reduction in the number of DC derived from myeloid precursors (18), which also have a more mature phenotype and an impaired ability to produce IL-12 with age (17,108). Other functions such as macropinocytosis, endocytosis, response to chemokines, and cytokine secretion are impaired, probably as a consequence of decreased activation of the phosphoinositide-3 kinase pathway (2). Together, these data suggest that some age-associated immune dysfunctions can originate from impaired DC functions.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Moreover, aging is associated with a reduction in the number of DC derived from myeloid precursors (18), which also have a more mature phenotype and an impaired ability to produce IL-12 with age (17,108). Other functions such as macropinocytosis, endocytosis, response to chemokines, and cytokine secretion are impaired, probably as a consequence of decreased activation of the phosphoinositide-3 kinase pathway (2). Together, these data suggest that some age-associated immune dysfunctions can originate from impaired DC functions.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Several reports indicate that there are no significant differences in numbers of circulating myeloid and plasmacytoid DCs between older people and young subjects and that the www.intechopen.com expression of costimulatory molecules (CD86 and HLA DR) is similar (Agrawal et al, 2007a;Agrawal et al, 2007b;Pietschmann et al, 2000). In contrast, another study showed that numbers of myeloid DCs progressively declined with age while proportion of plasmacytoid DCs was unaffected.…”
Section: Dendritic Cellsmentioning
confidence: 80%
“…Several studies used these in vitro cultured cells to assess the phenotype and functions of DCs in aged populations. Monocytederived DCs present no clear differences of costimulatory or activatory molecules (HLA-DR, CD80, CD86, CD40, CD83) except for CD25 and ICAM after lipopolysaccharide stimulation in healthy older individuals compared to younger (Agrawal et al, 2007b;Ciaramella et al, 2011;Agrawal et al, 2007a). Monocyte-derived DCs of older people are less efficient for micropinocytosis and phagocytosis of apoptotic cells and are impaired for migration (Agrawal et al, 2007b).…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 2 more Smart Citations